Progress in ethical practices of businesses - Serrano Santoyo, Arturo; Kuri-Alonso, Ingrid; Durazo-Watanabe, Eduardo; Rojas Mendizábal, Verónica Alexandra (Springer, 2021)
The purpose of this contribution is to develop an exploratory framework to analyse the ethical implications of the adoption of emerging digital technologies (EDT) by society. We posit that the exponential growth and dynamics of change of technologies such as arti!cial intelligence (AI), big data and the Internet of Things, among others, are of such magnitude and depth that many of the phenomena generated in the process of adopting these technologies have not been studied with suficient breadth, scrutiny and critical analysis, particularly in the contexts of emerging economies. In order to develop the proposed framework, we draw on the principles of complex systems to analyse the interactions of relevant agents of the digital ecosystem under study. Our exploration identi!ed a set of strongly related implications circumscribed to education, ethical and moral development, and regulation. It is suggested that the proposed framework may provide an initial platform for formal discussions and conversations towards understanding and applying EDT in a balanced and ethical manner. RESUMEN El propósito de esta contribución es desarrollar un marco exploratorio analizar las implicaciones éticas de la adopción de tecnologías digitales emergentes (EDT) por parte de la sociedad. Planteamos que el crecimiento exponencial y la dinámica de cambio de tecnologías como la inteligencia artificial (IA), big data e Internet de las Cosas, entre otras, son de tal magnitud y profundidad que muchos de los fenómenos generados en el proceso de adopción estas tecnologías no han sido estudiadas con suficiente amplitud, escrutinio y análisis crítico, particularmente en los contextos de las economías emergentes. Para desarrollar el marco propuesto, nos basamos en los principios de los sistemas complejos para analizar las interacciones de los agentes relevantes del ecosistema digital en estudio. Nuestra exploración identificó un conjunto de implicaciones fuertemente relacionadas circunscritas a la educación, el desarrollo ético y moral y la regulación. Se sugiere que el marco propuesto puede proporcionar una plataforma inicial para discusiones y conversaciones formales hacia la comprensión y aplicación de EDT de una manera equilibrada y ética.
Ethical Implications Regarding the Adoption of Emerging Digital Technologies: An Exploratory Framework
Chapter 12 Pages 219 - 239
Keywords: Digital technologies; Digital ethics; Policy and regulatory frameworks; Technology adoption; Sistema